TDS and pH Analysis for Water Quality Monitoring in Water Hydraulics Food Processor - Yusof, Ahmad Anas; Bakri, Syarizal; Misha, Suhaimi (International Journal of Integrated Engineering, 2019)
This study proposes a low-cost water hydraulics food processor for a traditional cookies production. The hygienic, safe and low maintenance cost characteristics of water should provide interesting viewpoints due to concern over issues in hydraulic fluid contamination, flammability, disposal, and costly maintenance. The objective of this project is to introduce the design and the working principle of the water hydraulics-driven food processor, and to determine production process performances and capabilities. In this paper, results of the corrosion monitoring of the test bed is presented. PLC is used in the testing of the machine, by creating an automatic movement of the cylinders. The Total Dissolved Solids (TDS) and pH analysis of the water hydraulics quality used in the process is discussed.